Developing Augmented Reality as a Teaching Material to Enhance Cultural Awareness in Secondary Schools - Pattaufi, -; Makawi, Faizal Erlangga; Aswan, Dedy; Cahyadi, Dian (JOIV : International Journal on Informatics Visualization, 2025)
This study investigates the development of Augmented Reality (AR)-based teaching materials to enhance students’ understanding of local wisdom and cultural diversity in secondary schools in South Sulawesi, Indonesia. Employing a quasi-experimental design, the research involved 304 students across four major ethnic regions, namely Makassar, Bone, Toraja, and Mandar, which were divided equally into experimental and control groups. The experimental group utilized AR-integrated materials, whereas the control group employed traditional methods. Data were collected through pre-tests, post-tests, and student perception surveys. Results revealed a significant increase in students' cultural awareness and understanding after the intervention, particularly among Bugis Makassar and Bugis Bone groups. The mean improvement in the experimental group was statistically significant (p < 0.001), confirming the pedagogical benefits of AR in promoting cultural literacy. Additionally, students expressed strong appreciation for AR’s interactive features, which enhanced their engagement and motivation. This study underscores the importance of integrating AR and local wisdom in educational content to foster inclusive, culturally responsive learning environments. The findings emphasize that augmented reality (AR)-based instructional resources serve as a powerful tool in enhancing students' understanding of indigenous knowledge and cultural diversity within secondary education. The incorporation of local wisdom into educational content not only enhances students’ learning experiences but also cultivates a profound appreciation of their cultural heritage. The results highlight the potential of AR as a transformative technology that can bridge the deficiencies inherent in conventional pedagogical approaches, particularly in fostering cultural awareness among learners.